Nigella Sativa Seed Extract Ointment Increasing the Amount of Healing Fibroblast and Collagen on Balb/C Mice - Mastuti, Sri; Hadi, Djoko Tri; Chodidjah, Chodidjah (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2017)
Introduction: Untreated cuts in some period of time, caused by various reasons, can be a problem. Alternative therapy used to speed up the healing of the cut is Nigella Sativa (NS).Objective: to investigate the number of fibroblast and collagen by giving 40% and 60% NS seed extract on the cut.Methods: post test only control group design, 48 male balb/c strain rats were divided into 2 large groups, with each cage contained 24 rats. Each group then divided to 4. Each group is subdivided into 4. Nigella sativa seed extract ointment with a concentration of 40% (NS-40) and 60% (NS-60) smeared 3x daily for 7 days (fibroblasts) and 14 days (collagen). Evaluation derived from preparations using HE staining and Masson’s Trichrome respectively.Results: Mann Whitney analysis shows that the number of fibroblasts and collagen in the CG group, NS-40, and NS- 6 0 Higher than CN, P <0.05.The number of fibroblasts in the NS-40 and NS-60 was not significantly different compared to the CG, as well as CN-40 with CN-60, p> 0.05. While the number of collagen in CN-60 were significantly higher than CN-40, p<0.05.Conclusion : administration of Nigella sativa seed extract ointment with a concentration of 40% and 60% in cuts for 7-14 days increase the number of fibroblasts and collagen, resulting in a shorter healing period.